Hubungan Motion Graphic Sebagai Konten Promosi Sekolah di Media Sosial - Ali Alamsyah Kusumadinata; Ike Atikah Ratnamulyani; Muhamad Rendi Nurmansyah (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial, Universitas Negeri Jakarta, 2019)
Social media is one product of the development of technology wrote so rapidly. Social media can not be separated from the everyday human life, seen from the users of social media continues to grow every time. Various convenience perceived as benefits of social media in life. As the utilization of social media as a means of information dissemination promotion of a company or agency. Motion graphic is one form of digital content that are frequently exploited by an agency or company for delivery of broad information such as public service announcements, company profile, and media promotion. Social media can be utilized as dispersion media motion graphic content more broadly and efficiently.